2002
DOI: 10.1083/jcb.200202055
|View full text |Cite|
|
Sign up to set email alerts
|

Microtubule-associated protein 1B

Abstract: Giant axonal neuropathy (GAN), an autosomal recessive disorder caused by mutations in GAN, is characterized cytopathologically by cytoskeletal abnormality. Based on its sequence, gigaxonin contains an NH2-terminal BTB domain followed by six kelch repeats, which are believed to be important for protein–protein interactions (Adams, J., R. Kelso, and L. Cooley. 2000. Trends Cell Biol. 10:17–24.). Here, we report the identification of a neuronal binding partner of gigaxonin. Results obtained from yeast two-hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…MAPs, and the absence of these microtubulestabilizing interactions leads to cytoskeletal derangements or abnormalities in subcellular trafficking. This is not only reminiscent of the havoc wrought in the hereditary tauopathies and Alzheimer's disease, where the MAP, tau, is implicated, but is also in keeping with the finding that MAP1B might be directly involved in the cytoskeletal derangements of giant axonal neuropathy (51). This raises the possibility that alteration of MAP behavior may be common to many neurodegenerative disorders, including SCA1.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…MAPs, and the absence of these microtubulestabilizing interactions leads to cytoskeletal derangements or abnormalities in subcellular trafficking. This is not only reminiscent of the havoc wrought in the hereditary tauopathies and Alzheimer's disease, where the MAP, tau, is implicated, but is also in keeping with the finding that MAP1B might be directly involved in the cytoskeletal derangements of giant axonal neuropathy (51). This raises the possibility that alteration of MAP behavior may be common to many neurodegenerative disorders, including SCA1.…”
Section: Discussionsupporting
confidence: 69%
“…These findings are consistent with microarray studies that identified MAP1B as an FMRP RNA target (49,50). Perhaps the most compelling evidence that MAP1B, and particularly its light chain, is a hub for interactions with disease-causing proteins is the finding that the light chain of MAP1B interacts with gigaxonin, a protein that displays mutations in giant axonal neuropathy (51). This progressive, autosomal recessive disease afflicts the central and peripheral nervous systems and is characterized by aggregation of cytoskeletal components, particularly intermediate filaments, to such an extent as to cause an increase in axonal diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of MAP1B in Lewy bodies indicates that overexpression of MAP1B might be involved in the formation of Lewy bodies (21). Mutations of gigaxonin induce giant axonal neuropathy via loss of gigaxonin-MAP1B light chain interactions (35). MAP1B, whose isoforms are not clearly defined, is up-regulated in the immediate-early phase of apoptosis in cerebellar granule neurons deprived of potassium and serum (36).…”
Section: Discussionmentioning
confidence: 99%
“…To understand how BPAG1n4 associates with vesicles, we initiated a yeast two-hybrid screen (13) with the BPAG1n4 ERM2 domain (amino acids 4680-5416) [supporting information (SI) Fig. 6] as bait.…”
Section: Resultsmentioning
confidence: 99%